2022
DOI: 10.15376/biores.17.3.4763-4780
|View full text |Cite
|
Sign up to set email alerts
|

Halostability and thermostability of chitinase produced by fungi isolated from salt marsh soil in subtropical region of Saudi Arabia

Abstract: Strategies based on halo- and thermostable enzymes are promising and attractive for biotechnological applications. Three fungal isolates, namely Aspergillus flavus, Cladosporium cladosporioides, and Alternaria alternata, and were subjected to chitinase production using a medium with different concentrations of NaCl up to 10%. C. cladosporioides was found to be the main chitinase producer at high concentration of NaCl; therefore, its identification was confirmed using 18S rDNA. The highest chitinase production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The property of enzyme thermal stability may depend on the fungus producer as previously mentioned and exposure time to temperature (Xia et al 2001;Farag et al 2016). Thermal stability studies indicated that chitinase of C. cladosporioides (Al Abboud et al 2022), Trichoderma viride (Ekundayo et al 2016), Penicillium chrysogenum (Atalla et al 2020), and A. flavus (Beltagy et al 2018) was stable up to 50 ºC. The high activity of thermostable chitinase at higher temperatures, in agreement with Guo et al (2008), gave it remarkable benefits over industrial catalysis.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The property of enzyme thermal stability may depend on the fungus producer as previously mentioned and exposure time to temperature (Xia et al 2001;Farag et al 2016). Thermal stability studies indicated that chitinase of C. cladosporioides (Al Abboud et al 2022), Trichoderma viride (Ekundayo et al 2016), Penicillium chrysogenum (Atalla et al 2020), and A. flavus (Beltagy et al 2018) was stable up to 50 ºC. The high activity of thermostable chitinase at higher temperatures, in agreement with Guo et al (2008), gave it remarkable benefits over industrial catalysis.…”
Section: Resultsmentioning
confidence: 94%
“…The thermal stability of chitinase was assessed, where the obtained enzyme was incubated at separate temperature from 10 °C up to 70 °C for 60 min, and then utilized a water bath (WBL-10LC-SSD1, LW Scientific, Lawrenceville, GA, USA). Activity of enzyme was detected as mentioned previously (Al Abboud et al 2022).…”
Section: Chitinase Production and Its Thermal Stability At Different ...mentioning
confidence: 99%
“…Amylases from fungi are widely applied for the formulation of oriental foods (Sidar et al 2023). According to several studies, fungi such as Aspergillus niger may synthesise a variety of enzymes to hydrolyse complex polysaccharides into simple compounds, which are then utilized for development and reproduction (Abdelghany and Bakri 2019;Al Abboud et al 2022;Bakri et al 2022;Al-Rajhi et al 2022a, 2022b. Several investigations tried bread waste as raw substrates for enzyme creations, including protease and glucoamylase, utilizing different microorganisms such as Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the silico protocol was applied to select the most suitable structures for biological observation of active compounds; this protocol was dependent on the correlation among biological activity values of the input structures and the target proteins in pathogenic organisms, cancer cells, etc. [ 20 , 21 , 22 , 23 , 24 , 25 ]. The present investigation was designed to explore the phytochemical characterization of M. pulegium extract by GC-MS and HPLC, studying different biological applications comprising antitumor, antimicrobial, anti-hemolytic and anticoagulant activities.…”
Section: Introductionmentioning
confidence: 99%